PENGARUH TEKNIK KURSI KOSONG TERHADAP PENINGKATAN KOMUNIKASI ASERTIF SISWA SMPN 34 PEKANBARU - Lestari, Tri; Yakub, Elni; Saam, Zulfan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the effect of applying individualcounseling with empty chair techniques to improve assertive communication. The research method used was experimental research that was analyzed in a mixture of qualitative and quantitative. The research subjects were selected through the results of low assertive communication questionnaires from 4 students in 34 Pekanbaru State Junior High Schools. The research design used by researchers is pre-test post-test one design group which is done twice, that is before being treated or pre-test and afterbeing treated (post-test) with one group of subjects. This research was conducted by providing 6 modified individual counseling services. The results of this study indicate that there is an influence of the empty chair technique on the increase in assertive communication based on an increase in assertive communication scores after the empty chair technique is performe.Key Words: Empty Chair Technique, Assertive Communication, Individual Counseling